Salvia changchuniana (Lamiaceae), a new species from Zhejiang, East China - Jin, Xiao-Feng; Ding, Bing-Yang; Chen, Zheng-Hai; Xu, Yue-Liang; Lu, Kai-Xing (Phytotaxa, 2023)
Salvia changchuniana (Lamiaceae), a new species from Zhejiang Province of eastern China, is described with illustrations. The new species is similar to Salvia liguliloba, but differs in having wider leaves, basal leaf blade ovate-elliptic, ovate-oblong or broadly ovate, 7‒13 cm long, 4‒9 cm wide, cauline leaf blade ovate-elliptic, ovate or broadly ovate, 9.5‒13(‒20) cm long, 4.5‒7(‒12) cm wide, inflorescence rachis densely recurved pubescent and glandular, calyx glandular externally, with ribs short-hispidulous, corolla short, 1.3‒1.5 cm long, tube pubescent externally, limb villous and glandular externally, middle lobe of lower lip compressed rounded-spathulate, ca. 3 mm long, ca. 2.5 mm wide, margin praemorse. All species of Salvia ser. Ligulilobae were compared with the new species.